The Factors Determining the Creativity of the Human Capital in the Conditions of Sustainable Development - Sipa, Monika (European Journal of Sustainable Development, 2018)
Sustainable development and innovativeness are challenges which contemporary enterprises and economies have to face. The increase in the innovativeness requires proper resources, in particular, creative and innovative human capital towards whom principles of responsibility are applied. Broadening the knowledge on the subject of creativity processes, creation and innovativeness will allow for the accomplishment of more productivity of human resources in the enterprise. Capital of knowledge and innovative capital will be more considerable. The main goal of the compilation was, therefore, to identify the factors determining creativity and innovativeness of labour resources in Polish and Slovakian economic entities. An analysis was conducted which allowed for the indication of both similarities and differences occurring in this area within the examined countries. The conclusions were based on the author?s own research which was carried out in the first quarter of 2017. Key words: creativity, human capital, innovativeness enterprises, sustainability development.